EFFECT OF ORGANIC AND MICROBIOLOGICAL FERTILIZER ON MORPHOLOGICAL AND PRODUCTIVE CHARACTERISTICS OF TRITICALE IN ORGANIC FARMING SYSTEM - Roljević Nikolić, Svetlana M; Dolijanović, Željko K.; Zečević, Veselinka M.; Puvača, Nikola M.; Oljača, Snežana I.; Šeremešić, Srđan I. (Journal of Agricultural Sciences (Belgrade), 2022)
Triticale (× Triticosecale Wittmack) is a type of cereal which is mainly used as animal feed. However, in the last few years there has been the growing interest in cultivating triticale for food production, particularly among organic farmers. The aim of the study was to examine the impact of biohumus and biofertilizer on morphological and productive characteristics of triticale depending on meteorological conditions during a three-year period (2009/10-2011/12). A two-factorial field experiment was arranged using a randomized block design with four replications. The object of the study was the triticale winter cultivar Odisej, and the impact of the following treatments was examined: a control variant without fertilization, biofertilizer (5.0 l ha-1), biohumus (3.0 t ha-1)+biofertilizer (5.0 l ha-1). The results showed that the expression of the examined characteristics was significantly affected by the environment. The lowest values were obtained in the first year, which had the most unfavourable meteorological conditions. Fertilization had a positive but not statistically significant impact on all characteristics. The application of biofertilizer had no impact on the stem length and grain weight per spike, but it significantly increased the number of fertile spikelets (3.7%), spike length (7.7%) and grain yield (18.6%). The combined application of fertilizers provided better results for all the examined characteristics, while in comparison with the control the differences ranged from 4.3% for the number of fertile spikelets to 46.5% for grain yield. The strongest correlation was determined between the spike length and number of fertile spikelets (r = 0.939**). The obtained results lead to the conclusion that under variables environmental conditions the application of well-balanced formulas of organic and microbiological fertilizers has a significant impact on morphological and productive characteristics of triticale, and consequently on the stability of this crop production in organic farming system.